Peran pendidikan Agama dan Kewarganegaraan di SMA dalam meningkatkan karakter tangguh, kompetitif, dan dinamis - Wulandari, Antonia P. J.; Astrini, Astrini (Konsorsium Psikologi Ilmiah Nusantara, 2013)
The research looked at the role of religious and citizenship educations acquired during high school in improving the characters in particular tough, competitive, and dynamic. The study was conducted on 100 freshmen at Binus University based on their perceptions of Religious and Citizenship education that they acquired during High School in improving tough, competitive, and dynamic characters. The results showed that they have all three characters, but the intensity is not strong and there was no signiicant relationship between perceptions of the two subjects with the characters. This suggests that student’s characters, tough, competitive and dynamic, are not based on whether they perceive the two subjects as pleasant or unpleasant. The formation of the characters in particular, tough, competitive and dynamic characters, can develop due to the circumstances of the school as a whole and not speciically through the subjects of Religious and Citizenship Educations.